Hyper-acute rejection following single lung transplantation: a case report - Samano, Marcos Naoyuki (2006)
Introduction: Immediate graft failure due to hyper-acute rejection is an already known phenomenon in cardiac, renal and hepatic transplantation. It is a rare occurrence in lung transplantation, with few cases described in the international literature. Purpose: We described a case of single lung transplant due to Chronic Obstructive Pulmonary Disease which evolved to fatal hyper-acute rejection a few hours after the operation. Methods: A 36-year old male patient with Chronic Obstructive Pulmonary Disease and indication for lung transplantation, whose initial assessment showed a negative pane-reactive antibody, and became positive after blood transfusions. The patient was submitted to a one-sided left single-lung transplant with no intercurrence. However, he presented a fast deterioration of his breathing parameters, with progressive radiographic infiltration up to a complete opacification of the transplanted lung. The patient died nine hours following the transplantation, despite the optimization of the parameters. Results: Histopathological and immunohistochemical analysis revealed signs of hyper-acute rejection by an intense fibrin deposition, dense neutrophilic infiltrate, and strong positivity of the fibrinogen to the immunofluorescence, and these signs were not present in the ischemia-reperfusion lesion. Conclusion: Although the hyper-acute rejection has lower incidence in the lung transplantation, it represents a lethal and severe complication. The accomplishment of the panel-reactive antibody is very important to quickly establish an aggressive immunossupressant therapy.